1992
DOI: 10.1042/bj2870247
|View full text |Cite
|
Sign up to set email alerts
|

Plasma clearance and net uptake of α-tocopherol and low-density lipoprotein by tissues in WHHL and control rabbits

Abstract: The mechanism(s) of uptake of vitamin E (alpha-tocopherol) by tissues is poorly understood. It has, however, been suggested from studies in vitro that the apolipoprotein B/E (apo B/E) receptor pathway for low-density lipoprotein (LDL) may be involved. To investigate the role of the apo B/E receptor pathway in vivo, we have studied the transport and uptake of alpha-tocopherol by tissues in Watanabe Heritable Hyperlipidaemic (WHHL) rabbits, which lack functional LDL (apo B/E) receptors, and controls. [3H]alpha-T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 27 publications
3
26
0
Order By: Relevance
“…These results confirm and extend previous reports suggesting that SR-BI-mediated uptake of vitamin E from HDL is physiologically important (21,29). This notion is also supported by the observations that in vivo, disruption of SR-BI expression causes a reduction in tocopherol levels (39), whereas defects in the LDL receptor do not impact tissue uptake of vitamin E (40). Furthermore, our data demonstrate that TTP is not essential for tocopherol uptake from LDL or HDL in hepatocytes.…”
Section: Discussionsupporting
confidence: 81%
“…These results confirm and extend previous reports suggesting that SR-BI-mediated uptake of vitamin E from HDL is physiologically important (21,29). This notion is also supported by the observations that in vivo, disruption of SR-BI expression causes a reduction in tocopherol levels (39), whereas defects in the LDL receptor do not impact tissue uptake of vitamin E (40). Furthermore, our data demonstrate that TTP is not essential for tocopherol uptake from LDL or HDL in hepatocytes.…”
Section: Discussionsupporting
confidence: 81%
“…In this animal model, a significant decrease in LDL ␣-tocopherol clearance, paralleling the inherent holoparticle clearance defect, was found [31]. Remarkably, WHHL rabbits exhibited no overt defect in tissue ␣-tocopherol levels except for a mild reduction in adrenal ␣-tocopherol content [32].…”
Section: Uptake By Receptor-mediated Lipoprotein Endocytosismentioning
confidence: 91%
“…The physiological relevance of this pathway for in vivo ␣-tocopherol transport was assessed in LDLR-deficient Watanabe heritable hyperlipidaemic (WHHL) rabbits [31,32]. In this animal model, a significant decrease in LDL ␣-tocopherol clearance, paralleling the inherent holoparticle clearance defect, was found [31].…”
Section: Uptake By Receptor-mediated Lipoprotein Endocytosismentioning
confidence: 99%
“…Kono et al [76] suggested recently that LDL particles carry the major portion of plasma α-TOH and that LDLR-mediated endocytosis contributes significantly to the uptake of α-TOH into cells [77] . However, studies performed on apolipoprotein B (Apob)-knockout mice and heritable hyperlipidemic Watanabe rabbits lacking the LDLR showed discrepancies in circulating α-TOH levels and tissue distribution, thus questioning the importance of LDL for α-TOH transport [78,79] . Cohn et al [79] therefore concluded that α-TOH in LDL can be taken up by tissues via LDLR but is also independent of this lipoprotein receptor.…”
Section: Vascular Transportmentioning
confidence: 99%
“…However, studies performed on apolipoprotein B (Apob)-knockout mice and heritable hyperlipidemic Watanabe rabbits lacking the LDLR showed discrepancies in circulating α-TOH levels and tissue distribution, thus questioning the importance of LDL for α-TOH transport [78,79] . Cohn et al [79] therefore concluded that α-TOH in LDL can be taken up by tissues via LDLR but is also independent of this lipoprotein receptor. Uptake transporters and specific intracellular transport proteins involved in α-TOH trafficking are handled in more detail in a following section.…”
Section: Vascular Transportmentioning
confidence: 99%